Cytotoxic Effects of Betulinic Acid and its Derivatives on Human Myeloid Leukemia (Hl-60) Cell Line - Faujan, Nur Hana (2008)
Betulinic acid (BA) is a triterpene from bark extracts of Melaleuca cajuputi Powell (Myretaceae) a Malaysian plant. The cytotoxic effects of betulinic acid (BA) and its four synthetic derivatives that has been modified at C-3 hydroxy group of BA (betulinic acid acetate (BAAC), 3-O-(2’,2’-dimethylsuccinyl)-betulinic acid (BAES), 3-O-succinyl-betulinic acid (BASUC) and betulinic acid benzoate (BCL) were screened on human myeloid leukemia (HL-60), human T4-lymphoblastoid (CEM-SS), BALB/c murine myelomonocytic leukemia (WEHI-3B), human cervical epithelial carcinoma (HeLa) human breast adenocarcinoma (MCF-7), mouse skin melanoma (B16), human glioblastoma (DBTRG0.5MG) cancer cell lines. Several derivatives elicited cytotoxicity as assessed by 3-[4,5-dimethylthizol-2-yl]-2,5-diphenyltetrazolium bromide (MTT) assay. Betulinic acid acetate (BAAC) was the most effective among the betulinic acid derivatives. It had the most potent cytotoxic activity against human myeloid leukemia (HL-60), human T4-lymphoblastoid (CEM-SS), BALB/c murine myelomonocytic leukemia (WEHI-3B) and human cervical epithelial carcinoma (HeLa) but not on normal human lymphocytes (PBMC), suggesting its action is specific for tumor cells. This study was focused on HL-60 that showed the most sensitive cell line after 72 hours of treatment with all betulinic acid derivatives. BA and BAAC inhibit HL-60 cell line after 72 hours treatment with IC50 values of 2.60 and 1.38 μg/mL, respectively. On microscopic examination, both compounds exhibited characteristic morphological features of apoptosis, such as cell shrinkage and formation of apoptotic bodies. Fluorescent staining with acridine orange (AO) and propidium iodide (PI) revealed distinct chromatin condensation and nuclear fragmentation. The internucleosomal DNA fragmentation was confirmed by the pattern of DNA laddering into fragments with multiples of 180-220 base pairs detected in agarose gel electrophoresis. The induction of apoptosis was also confirmed by flow cytometric analysis of the cell cycle. BA and BAAC were shown to induce a time dependent increase in the sub G1 peak indicating apoptotic phenomenon as obtained from the DNA content histogram analysis. BA and BAAC were marked as cytotoxic agent induced by apoptosis.